THE ROLE OF CHEST RADIOGRAPHY TO DIAGNOSE LARGE PERICARDIAL EFFUSION IN WOMAN 66 YEARS OLD WITH MALIGNANCY : HIDING PERICARDIAL EFFUSION - Ilzy Jum Ahmad; Tito Armando; Fadliah Abadi (Universitas Negeri Gorontalo, 2022)
Introduction: Pericardial effusion refers to an increase in fluid accumulation in the pericardial cavity. This pericardial fluid acts as a lubricant between the layers of the pericardium. We report a case of pericardial effusion, which was significant but not detectable on conventional chest radiographs.Case: A 66-year-old woman with lung adenocarcinoma accompanied by large pericardial effusion without sign of impending tamponade. The diagnosis of pericardial effusion was mainly based on echocardiography, where there is a large pericardial effusion but without signs of cardiac tamponade, and the patient then underwent pericardiocentesis. Previously, the patient had undergone two examinations with two different imaging modalities, namely CXR and chest CT scan, where on the CXR results, the patient only showed cardiomegaly.Discussion: There are four parameters suggestive for assessing a pericardial effusion, namely enlargement of the heart silhouette, pericardial fat stripe, left dominant pleural effusion, and an increase in the transverse diameter of the heart compared to the previous chest X-ray. This parameter is obtained not only based on the position of the photo taken but requires another position, whereas, in this patient, only CXR was performed with the posteroanterior position.Conclusion: When there are complaints of progressive shortness of breath in individuals with an underlying disease that may cause pericardial effusion, then the CXR examination cannot be used as a reference when there are no radiographic signs that point to pericardial effusion because CXR has a low diagnostic value in assessing the presence of pericardial effusion.